Lipopolysaccharide- and p38 MAPK-mediated signaling of the Heme oxygenase-1 (HO-1) gene in macrophages - Vijayan, Vijith; Justus Liebig University Giessen (My University, 2012)
Monocytes or macrophages are crucial regulators of inflammation. Intracellular signaling in macrophages is tightly regulated to ensure that they do not undergo excessive activation, which may lead to chronic inflammation accompanied with potential damage to the host tissue. Induction of HO-1 in macrophages has been shown to have potent immunomodulatory properties.In this thesis two different signalling mechanisms are described which lead to the induction of HO-1 in macrophages. In the first part the signalling pathway leading to the induction of HO-1 via toll-like receptor (TLR)4 by the classical pro-inflammatory stimulus lipopolysaccharide (LPS) is described. The second part of this thesis deals with the induction of HO-1 caused by the inhibition of the mitogen activated protein kinase (MAPK) p38.Induction of HO-1 by LPS in macrophages has been described earlier, but the exact regulatory mechanisms of this pathway are not well understood. In this thesis it is shown that Bruton s tyrosine kinase (Btk) mediates the LPS-induction of HO-1. LPS-dependent induction of HO-1 was blocked in macrophages treated with the Btk inhibitor, LFM-A13 or in Btk alveolar macrophages. Promoter studies and quantitative real time PCR studies revealed a transcriptional regulatory mechanism. Btk was shown to mediate the production of ROS and activation of the transcription factor Nrf2.p38 MAPK inhibition is shown to increase the expression of HO-1. This was rather surprising, because activation of p38 MAPK has earlier been shown to mediate HO-1 induction caused by various stimuli. This increase in HO-1 expression was also observed in p38mouse embryonic fibroblasts. Further analysis revealed that p38 inhibition leads to an increased production of reactive oxygen species (ROS) and activation of Nrf2. Furthermore, ERK MAPK was also shown to be involved in this pathway.Taken together, this thesis demonstrates that signaling to HO-1 in macrophages is primarily mediated by the transcription factor Nrf2. Further studies to unravel the regulation of this gene may help to develop novel strategies for clinical intervention in inflammatory disorders.

Monozyten und Makrophagen spielen eine bedeutsame Rolle für die Regulation von Entzündungsreaktionen. Die intrazelluläre signaltransduktion in Makrophagen wird streng reguliert, um eine überschießende Aktivierung dieser Zellen zu vermeiden, die zu einer chronischen Entzündung mit möglicher Gewebeschädigung führen könnte. Für die Induktion der Hämoxygenase (HO)-1 in Makrophagen konnte eine wirksame immunmodulatorische Wirkung gezeigt werden.In der vorliegenden Arbeit werden zwei verschiedene Signalübertragungwege beschrieben, die zu einer Induktion der HO-1 in Makrophagen führen. Im ersten Teil der Arbeit ist ein Signalweg beschrieben, der zu einer Induktion der HO-1 über eine Aktivierung von Toll-like Rezeptor (TLR)-4 durch den klassischen pro-inflammatorischen Stimulus Lipopolysaccharid (LPS) führt. Der zweite Teil der Arbeit beschäftigt sich mit der Induktion der HO-1 durch die Inhibition der Mitogen-aktivierten Proteinkinase (MAPK) p38.Die Induktion der HO-1 durch LPS wurde bereits früher erstmals beschrieben, aber die genauen regulatorischen Mechanismen sind nicht genau bekannt. In der vorliegenden Arbeit wurde gezeigt, dass die Bruton-Tyrosinkinase (Btk) die LPS-abhängige Induktion der HO-1 vermittelt. Die HO-1 Induktion durch LPS wurde durch Behandlung von Makrophagen mit dem Btk Inhibitor LFM-A13 oder in Btk-/- Alveolarmakrophagen blockiert. Promoterstudien und quantitative real time PCR Studien zeigten einen zugrundeliegenden transkriptionalen Mechanismus.Weiterhin konnte gezeigt werden, dass die Inhibition der p38 MAPK die HO-1 Expression heraufreguliert. Dieser Befund war unerwartet, weil in früheren Untersuchungen gezeigt worden war, dass p38 Aktivierung die Induktion der HO-1 vermittelt hatte. Diese HO-1 Induktion konnte auch in p38-/- murinen embryonalen Fibroblasten beobachtet werden. Weitere Untersuchungen zeigten, dass die Inhibition von p38 zu einer gesteigerten Produktion von reaktiven Sauerstoffspezies (ROS) und einer Aktivierung von Nrf2 führte. Außerdem konnte gezeigt werden, dass die MAPK ERK an dieser Regulation beteiligt war.Zusammenfassend zeigt diese Arbeit, dass die signaltransduktion zum HO-1 Gen in Makrophagen in erster Linie durch den Transkriptionsfaktor Nrf2 vermittelt wird. Weitere Studien zur Aufklärung der genauen Regulation dieses Genes könnten dabei helfen, neue Behandlungsstrategien bei der entzündlichen Erkrankungen zu entwickeln.
Keywords: ddc:610